PELAKSANAAN PROGRAM KESEJAHTERAAN DAMPAKNYA TERHADAP DISIPLIN KERJA KARYAWAN PADA KANTOR PUSAT PT. OTO FINANCE BANDUNG The Application Of Prosperity Programs Has Effect To Employees Discipline At Head Office PT. Pos Indonesia, Ltd Bandung - Lita Wulantika; Sri Haryanti (JURISMA : Jurnal Riset Bisnis & Manajemen, 2015)
The Implementation of employee’s welfare programs should be developed based on legal regulations, based on berasaskan fairness and feasibility, and guided by the ability of the company. The goal is to create employee’s discipline. The purpose of this research is to understand the implementation of welfare programs. Employee’s discipline and examine the impact of the implementation of welfare programs to discipline employees at the Head Office of PT. Oto Finance Bandung. ……………The method that is used in this research descriptive and quantitative research approaches. The population in this research is 410, and using the propotionate stratified random sampling technique (stratified random sample) in order to obtain 80 employees as sample. Techniques of data collection are using interviews, observation, questionnaires, and documentation. Analysis method using Pearson correlation and coefficient of determination, as well as t test using SPSS 12.0 for windows. …………………………………………………………………………………………………………….             The results mentioned implementation of employee benefit programs based on the responses of respondents with good results, while the employee disciplinary showed good results. The results shows strong relationship between the implementation of welfare programs and employees discipline, with contributions amounting to 63% impact, and the remaining 37% is another factor which is not examined by authors such as loyalty, motivation, morale, job satisfaction and others. ……………………………………………………………………………………………………………..   Keywords : Welfare Programs, Work Discipline, and the Central Office Employee of PT. Pos Indonesia, Ltd Bandung.